Ethical aspects in the prevention of insulin-dependent diabetes mellitus - Manna, Raffaele; Migliore, Alberto; Serra, Angelo (Medicina e Morale, 1988)
Insulin-dependent diabetes mellitus (IDDM) seems to be on the rise today, especially in northern European populations. IDDM is a disease that leads to numerous complications (e.g., metabolic decompensation, macroangiopathy, microangiopathy, retinopathy, nephropathy etc.) and requires the individual to be on daily insulin administration, for life.